Peningkatan Kesadaran Hukum Masyarakat dalam Pencegahan dan Solusi Akibat Hukum Perkawinan yang Tidak Tercatatkan di Desa Sungai Nipah, Kecamatan Siantan, Kabupaten Mempawah - Prihatin, Angga; Marnita; Susila, Sugeng (Indra Institute Research & Publication, 2024)
Sungai Nipah Village, which is located in Mempawah Regency, is one of the areas that has problems with unregistered marriages due to unregistered marriages. unregistered marriages can give rise to issues regarding the rights of wives, children, as well as other legal consequences in civil law. The aim of this service activity is to provide understanding to the public about the legal consequences of unregistered marriages, preventing the occurrence of unregistered marriages. not registered, as well as providing solutions to the community to solve legal problems that arise as a result of unregistered marriages. This activity is carried out using methods of socialization activities, interactive discussions, and mentoring. The result of service activities is an increase in legal knowledge by Village Officials and Village residents to be able to help residents with problems regarding the implementation of unregistered marriages in the community, as well as being able to provide direction as well as solutions and legal remedies that can be taken for unregistered marriages.